Associations of Public Transportation Use With Cardiometabolic Health: A Systematic Review and Meta-Analysis. Issue 4 (25th January 2019) - Patterson, Richard; Webb, Elizabeth; Hone, Thomas; Millett, Christopher; Laverty, Anthony A
Abstract: Public transportation provides an opportunity to incorporate physical activity into journeys, but potential health impacts have not been systematically examined. We searched the literature for articles on public transportation and health published through December 2017 using Google (Google Inc., Mountain View, California), 5 medical databases, and 1 transportation-related database. We identified longitudinal studies which examined associations between public transportation and cardiometabolic health (including adiposity, type 2 diabetes mellitus, and cardiovascular disease). We assessed study quality using the Newcastle-Ottawa Scale for cohort studies and performed meta-analyses where possible. Ten studies were identified, 7 investigating use of public transportation and 3 examining proximity to public transportation. Seven studies used individual-level data on changes in body mass index (BMI; weight (kg)/height (m) 2 ), with objective outcomes being measured in 6 studies. Study follow-up ranged from 1 year to 10 years, and 3 studies adjusted for nontransportation physical activity. We found a consistent association between use of public transportation and lower BMI. Meta-analysis of data from 5 comparable studies found that switching from automobile use to public transportation was associated with lower BMI (−0.30 units, 95% confidence interval: −0.47, −0.14). Few studies have investigated associations between public transportation use and nonadiposity outcomes. These findings suggest that sustainable urban design which promotes public transportation use may produce modest reductions in population BMI.